Beyond MechanizationBeyond Mechanization by HirschhornLarry. Cambridge, MA: MIT Press, 1984, 187 pp., $17.50, cloth. - Adler, Paul S. (Academy of Management Review, 1986)
The article reviews the book ?Beyond Mechanization,? by Larry Hirschhorn.